Mathema’s tics in the cultural manifestation of Zambiapunga: A Systematic Literature Review - José Lucas Matias de Eça; Zulma Elizabete de Freitas Madruga (Universitas Sarjanawiyata Tamansiswa, 2026)
The expression “mathema’s tics”, coined by Ubiratan D’Ambrosio, designates the etymological root of Ethnomathematics (ethno + mathema + tics), which means the set of techniques, arts, methods and ways of proceeding (tics) mobilized by a given social group (ethno) in the interpretation, understanding, explanation and management of its reality (mathema). Considering this concept, the present study aims to analyze how the mathematical practices present in the diverse repertoire of knowledge and practices originating from the Zambiapunga cultural manifestation have been discussed in literature. To this end, a systematic literature review was conducted on the cultural expression of Zambiapunga to establish a scientific epistemology, of a mathematical nature, based on the ancient knowledge and practices of Bakongo people produced and practiced within this ancestral tradition. To obtain the data, the main platforms in the educational context were used, both nationally and internationally, and analyzed using a qualitative approach. The review process returned 21 sources, which form the broader corpus of data. However, only four of these sources specifically address mathematical practices; therefore, they alone make up the corpus of analysis in this study. Findings show that Zambiapunga constitutes a fertile cultural field of mathematizations, which is expressed in the knowledge and practices of members of this centuries-old tradition and reveals formative potential emerging from its cultural dynamics. Furthermore, the analysis points to a low number of studies focusing on the mathematical knowledge and practices present in Zambiapunga. After all, this centuries-old tradition possesses a vast repertoire that can be mathematized, with the aim of contributing to the teaching and learning process of mathematics.